1998
DOI: 10.1016/s0969-2126(98)00149-x
|View full text |Cite
|
Sign up to set email alerts
|

Structures of the psychrophilic Alteromonas haloplanctis α-amylase give insights into cold adaptation at a molecular level

Abstract: . We propose that an increased resilience of the molecular surface and a less rigid protein core, with less interdomain interactions, are determining factors of the conformational flexibility that allows efficient enzyme catalysis in cold environments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
172
0
1

Year Published

1999
1999
2013
2013

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 209 publications
(178 citation statements)
references
References 53 publications
5
172
0
1
Order By: Relevance
“…For instance, all 24 residues forming the catalytic cleft (supplemental Fig. S1) and involved in substrate binding are strictly conserved in both the psychrophilic and the mesophilic homologues (11,24). This outstanding example of active site identity demonstrates that cold activity is reached without any amino acid substitution in the reaction center.…”
mentioning
confidence: 89%
See 2 more Smart Citations
“…For instance, all 24 residues forming the catalytic cleft (supplemental Fig. S1) and involved in substrate binding are strictly conserved in both the psychrophilic and the mesophilic homologues (11,24). This outstanding example of active site identity demonstrates that cold activity is reached without any amino acid substitution in the reaction center.…”
mentioning
confidence: 89%
“…The prevailing hypothesis assumes that cold-adapted enzymes have acquired a high catalytic activity at low temperature by improving their conformational flexibility at the expense of stability (7)(8)(9)(10). It has been shown that the crystal structure of psychrophilic enzymes is characterized by the disappearance of various noncovalent stabilizing interactions, resulting in both an improved dynamics of the enzyme conformation and in a weak stability (11)(12)(13)(14)(15)(16)(17). There is indeed a clear decrease in the number and strength of all known weak interactions and structural factors involved in protein stability, from thermophiles, mesophiles to psychrophiles (17)(18)(19).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Concerning Tris, which inhibits some GH13 enzymes (Aghajari et al 1998;Skov et al 2001), it was also tested and found to be more weakly bound (Ravaud et al 2007) than castanospermine and deoxynojirimycin. …”
Section: Biochemical Properties Of Sucrose Isomerasesmentioning
confidence: 99%
“…It is quite interesting that α -amylases from Antarctic bacterium displays approximately 66% amino acid similarity with porcine pancreatic α -amylase [51]. However the characterization of psychropilic α-amylases at 4 o C showed seven folds more kcat and kcat/Km values where as the stability was 10 kJ.mol -1 compared with porcine enzyme [52].…”
Section: Enzymes From Marine Cold Loving Microorganismsmentioning
confidence: 99%